Can Acute Care Biomarkers Change Patient’s Management in Sepsis? - Salvatore Di Somma; Luca Crisanti (Eurasian Journal of Emergency Medicine, 2022)

(untitled)
Sepsis and septic shock have an enormous burden on healthcare systems, having more than 30 million people worldwide suffering from those diseases. As emergency providers we must be able to immediately recognize the presence of sepsis to improve the management of this disease and reduce its burden on patient’s lives and on the emergency departments. Biomarkers can play an important role in this attempt. Laboratory tests could help both to identify the presence of sepsis at patients’ arrival and to stratify the risk of progression to septic shock. A new biomarker in that regard is represented by Bioactive Adrenomedullin (BioADM), which mirrors vascular integrity, and is able to detect the physio pathological deterioration of the patients with sepsis that will progress into septic shock. Now, thanks to point-of-care testing devices, we are able to measure BioADM in whole blood in less than twenty minutes, which will help the physician making faster and more adequate therapeutical decisions beside patient’s bed. The good news is that BioADM will also serve as a target for a monoclonal antibody that will counteract the vascular disfunction in septic shock. In conclusion, coupling BioADM with other biomarkers already routinely used such as procalcitonin and lactate we can immediately change patient’s management in Sepsis improving our decision making and patient outcome.